Modeling Factors Affecting Vocational School Students’ Perceived Ease of Use of Educational Technology - Masruri Hafid; Krismiyati Krismiyati; Andrushia Diana (International Journal of Information Technology and Business, 2025)
The integration of educational technology has become increasingly important in supporting effective learning processes. Google Drive is one of the widely used cloud platforms for online storage, access, and collaboration in educational activities. This study aims to examine the factors influencing vocational school students’ perceived ease of use (PEoU) of Google Drive as a learning support tool. The research model was adapted from the Technology Acceptance Model (TAM) by incorporating external variables, including Computer Self-Efficacy (CSE), Perceived Enjoyment (PE), Perceptions of External Control (PEC), Technological Complexity (TC), and Facilitating Conditions (FC). Data were collected from 274 students at a public vocational school in Central Java using an online questionnaire. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS. The findings reveal that Computer Self-Efficacy, Perceived Enjoyment, and Perceptions of External Control significantly influence students’ perceived ease of use of Google Drive. In contrast, Technological Complexity and Facilitating Conditions do not significantly affect perceived ease of use. These findings highlight the importance of internal user perceptions in supporting educational technology adoption among vocational school students.